Fundamentals and affordability in the U.S. housing market: 1991-2015 : A State-level analysis - Laaksonen, Niklas (My University, 2024)
Housing market fundamentals have a strong correlation with house prices. In the past few decades, housing affordability in the United States has been a key topic of discussion as homes have become more expensive. The housing market is central to any country, as everyone is a part of the housing market either through homeownership or renting. This study aims to find how fundamentals of the U.S. housing market have impacted housing prices between 1991-2015. In addition, affordability of housing will be considered using a home price-income ratio, calculated using the home price index and per capita income data. The U.S. housing market is considered on a state-level due to the heterogeneity of housing markets across the country. Panel regression analysis will be used to analyse the correlation between housing market fundamentals and house prices. The study finds that during the whole period of 1991-2015, income and population have a strong positive correlation with house prices, whereas unemployment has a negative correlation. The period of 1991-2015 was also split into three separate periods to compare results. The correlation coefficients during and after the financial crisis, 2008-2015, differed from the previous results, with income having negative correlation and population having weak positive correlation with housing prices. Housing affordability measured by the home price-income ratio deteriorated in the mid-2000’s prior to the financial crisis. Although a trend in the development of the home price-income ratio is found, there are states with clearly different outcomes. This study contributes to existing literature by emphasising the impact of housing fundamentals on the housing market and considering state-level differences in the United States.

Asuntomarkkinoiden perustekijöillä on vahva korrelaatio asuntojen hintojen kanssa. Asuntojen kohtuuhintaisuus on ollut keskeinen keskustelunaihe Yhdysvalloissa viime vuosikymmeninä asuntojen hintojen noustessa. Asuntomarkkinat ovat keskeisiä kaikissa maissa, sillä jokainen henkilö on osa asuntomarkkinoita joko omistamisen tai vuokrauksen kautta. Tämän tutkimuksen tavoitteena on selvittää kuinka Yhdysvaltojen asuntomarkkinoiden perustekijät ovat vaikuttaneet asuntojen hintoihin vuosina 1991–2015. Lisäksi asumisen kohtuuhintaisuutta tarkastellaan asunnon hinta-tulosuhteella, joka lasketaan asuntohintaindeksin ja asukaskohtaisten tulotietojen avulla. Yhdysvaltojen asuntomarkkinoita tarkastellaan osavaltiotasolla niiden heterogeenisyyden vuoksi. Paneeliregressioanalyysillä analysoidaan asuntomarkkinoiden perustekijöiden ja asuntojen hintojen välistä korrelaatiota. Tutkimus osoittaa, että vuosina 1991–2015 tuloilla ja väestönkasvulla oli vahva positiivinen korrelaatio asuntojen hintojen kanssa. Työttömyydellä oli negatiivinen korrelaatio asuntojen hintojen kanssa. Vuodet 1991–2015 on jaettu kolmeen eri ajanjaksoon tulosten vertailua varten. Korrelaatiokertoimet finanssikriisin aikana, ja sen jälkeen, poikkesivat aiemmista tuloksista, sillä tuloilla oli negatiivinen korrelaatio ja väestönkasvulla heikko positiivinen korrelaatio asuntojen hintojen kanssa. Asunnon hinta-tulosuhteella mitattuna asumisen kohtuuhintaisuus heikkeni 2000-luvun puolivälissä ennen finanssikriisiä. On kuitenkin olemassa osavaltioita, joiden asunnon hinta-tulosuhde poikkeaa maan keskiarvosta. Tämä tutkimus täydentää olemassa olevaa kirjallisuutta korostamalla asumisen perustekijöiden vaikutusta asuntomarkkinoihin ja huomioimalla osavaltiotason eroja Yhdysvalloissa.
Keywords: housing markets, macroeconomics, asuntomarkkinat, makrotaloustiede